Migrants' international transfers and educational expenditure: empirical evidence from Albania - Cristina Cattaneo (Fondazione Eni Enrico Mattei (FEEM), 2010)
The present paper analyses the expenditure behavior of Albanian families. The objective is to cast some light upon the relationship between education expenditure and the volume of remittances, sent from abroad by household members. To assess the existence of an education enhancing effect of remittances, an Engel curve framework is employed, where heterogeneity in interests or in bargaining power among the members within the households is assumed. The empirical estimation accounts for the censored nature of the education expenditure through using Heckman two-step as well as a semiparametric model for sample selection. Finally, quintile regression analysis is employed to investigate whether migrants' remittances have a differentiated effect on various quantiles of the conditional distribution of the education consumption.
Keywords: R; J; 330; Migrant Remittances; Engel Curves; Education expenditure; Rücküberweisung (Migranten); Bildungsinvestition; Mikroökonomische Konsumfunktion; Familienökonomik; Albanien